(untitled) (Journal of Environmental Science and Natural Resources, 2015)
An experiment was conducted on environmental implications and its impact on aquatic productivity in the southwest coastal region for a period of 2 months (May-June/2013). Five Rivers such as Pira River, Andarmanik River, Sonatala River, Khaprabhanga River and Rupsaha River were selected for sample collection and were treated as T1, T2, T3 T4 and T5. Three sampling sites were selected from each River based on salinity. The overall mean values of water temperature were 28.17 ±0.98, 27.41 ±1.21, 28.12 ± 1.11 and 27.13 ± 1.26, 26.62 ± 1.01 0C in treatment T1, T2, T3, T4 and T5, respectively. The mean values of water transparency of treatments T1 T2 T3 T4 and T5 were 36.00±1.26, 31.0±0.0894, 34.00±1.94, 28.00±1.46 and 31.00±1.86cm, respectively. The overall mean values of water temperature were 6.56 ± 0.12, 6.47 ±0.23, 6.34 ± 0.12, 6.19 ± 0.22, and 6.67 ± 0.29 ppm in treatment T1, T2, T3, T4 and T5 respectively. pH values were found to fluctuate from 6.72 to 7.64, 6.48 to 7.13, 6.95 to 7.35 and 6.86 to 7.6 in treatment T1, T2, T3, T4 and T5 respectively. Mean values of total salinity were 2.17 ±0.12, 6.17 ±0.82, 7.17 ±0.92, 10.17 ±0.1.12 and 1.78 ±0.12 mg/l in treatment T1, T2, T3, T4 and T5 respectively. Mean values of total alkalinity were 187.5±2.25, 165.5±3.1, 185.5±2.15, 175±2.5 and 180.5±3 mg/l in treatment T1, T2, T3, T4 and T5 respectively. Mean values of total alkalinity were 187.5±2.25, 165.5±3.1, 185.5±2.15, 175±2.5 and 180.5±3 mg/l in treatment T1, T2, T3, T4 and T5 respectively. Mean values of total alkalinity were 187.5±2.25, 165.5±3.1, 185.5±2.15, 175±2.5 and 180.5±3 mg/l in treatment T1, T2, T3, T4 and T5 respectively. Total hardness of water was found to range from 37 mg/l to199 mg/l. The mean values of NH3-N (mgl-1) were found to vary from 0.23 ± 0.03 ,0.27 ±0.08, 0.23 ±0.03, 0.25 ±0.03 and 0.27 ± 0.05 mgl-1 in treatment T1, T2, T3, T4 and T5 respectively. The mean values of nitrite (NO2) concentration were 0.63±0.06, 0.68 ±0.08, 0.67±0.09, 0.73±0.03 and 0.67±0.06 mgl-1 in treatment T1, T2, T3, T4 and T5 respectively. There were no significantly different of temperature, dissolved oxygen pH and alkalinity among the treatments but significance difference found in transparency, salinity, hardness, ammonia, nitrite using ANOVA (P<0.05). Ammonia and nitrite concentration of Rupsha River (T5) higher than other four Rivers due to municipal waste product of Khulna city. A proportionally strong relationship was found among salinity, transparency and hardness. Highest concentration of phytoplankton was found in Rupsha River (lowest salinity) and lowest phytoplankton concentration was found in Khaprabhanga River (highest salinity). DOI: http://dx.doi.org/10.3329/jesnr.v6i2.22099 J. Environ. Sci. & Natural Resources, 6(2): 71-78 2013